Detection of Amino Acid Mutations in Dihydrofolate Reductase & Dihydro Pteroate Synthase Gene in Plasmodium Vivax Isolates - Yasmin, Rizwana; Jehan, Musarrat; Kalam, Mehwish; Siddiqa, Syeda Mariam; Harani, Mahadev (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To assess the frequency and patterns of mutations and distribution of alleles in Plasmodium. Vivax Dihydrofolate Reductase (dhfr) & Dihydro Pteroate Synthase (dhps) genes in Karachi. Methodology: The descriptive cross-sectional study was carried out at the Department of Biotechnology, University of Karachi from June 2014 to February 2016. The sampling technique used was Non-probability convenient sampling method. A total of n=200 malaria cases irrespective of age and gender from Jinnah Medical College Hospital Korangi Karachi were selected. Around 200 µL of blood was collected in micro centrifuge tubes. Among them, 36 cases of P. vivax were detected by microscopy. DNA was extracted from these 36 samples followed by polymerase chain reaction (PCR) and sequencing of amplified genes of Plasmodium vivax Dihydrofolate reductase (pvdhfr) & Plasmodium vivax Dihydro pteroate synthase (pvdhp). Results: The analysis of 36 amplified P. vivax isolates revealed presence of various alleles of pvdhfr and pvdhps genes producing both wild type (W) and mutant amino acids having single, double & multiple mutations at multiple positions. In pvdhfr gene, common mutations were observed in ‘S’ amino acids at codons 58 &117 and ‘D’ at codons 105 &157. Regarding pvdhps gene, common mutations were observed in ‘V’ amino acids at codon 398 and ‘K’ at codon 590. Conclusion: The frequency and variety of mutations we detected in pvdhfr and pvdhps genes signify the drug resistance in plasmodium vivax so there is need of some measures to control drug resistance by better formulation using combination of drugs.